Implementasi Konsep Sajidin Dalam Surat Al-Hijr Ayat 98 Pada Dunia Pendidikan - Istiqomah rahmawati; Eko Ngabdul Shodikin; Sarwadi (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2022)
The word prostration in the Qur'an with its various forms, often experiences repetition in many verses, this indicates that the word has an important and deep meaning. This is what inspired the author to explore the concept of